Four-year injury survey in heptathlon and decathlon athletes - Edouard, P.; Kerspern, A.; Pruvost, J.; Morin, J.-B. (Science & Sports, 2012)
Background: Heptathlon and decathlon may pose a greater risk of injury to athletes than other track and field events due to the number and intensity of events and to the high level of physical and psychological demand.